FORECASTING HARVEST RESULTS OF FRESH FRUIT BUNCHES USING THE SES METHOD - Kurniawan, Ahmad; Helmiah, Fauriatun; Yuma, Febby Madonna (STMIK Royal, 2024)
Abstract: PT. Perkebunan Nusantara IV (Persero) Tinjowan is a state-owned enterprise unit operating in the palm oil plantation industry. In an effort to increase production, the plantation company aims to enhance production efficiency so that palm oil product prices become more competitive by determining harvest yields. The company's harvest yield estimation still uses a traditional approach based on the average bunch weight (BJR), considering the year of planting and the planting area. However, this technique is less effective and efficient. If the company's estimates are incorrect, it can potentially lead to losses or increased production budgets. The purpose of this research is to obtain a comparison of forecast results for the next month with the best alpha accuracy measure using the Single Exponential Smoothing method. The research method used is based on qualitative and quantitative data from interviews and observations of data from December 2022 to November 2023. The forecasting results with an alpha accuracy value of 0.9 using the Single Exponential Smoothing method show a forecast for December 2023 of 13,835.57844 with a percentage error rate (MAPE) of 9.28%, MAD of 1,021,423.6, and MSE of 174,130,366.Keywords: forecasting; palm oil; single exponential smoothing Abstrak: PT. Perkebunan Nusantara IV (Persero) Tinjowan sebagai unit usaha BUMN yang beroperasi di industri perkebunan kelapa sawit. Dalam upaya meningkatkan produksi, perusahaan perkebunan, peningkatan efisiensi produksi agar harga produk sawit lebih kompetitif dengan menentukan hasil panen. Pada perkiraan hasil panen perusahaan masih menerapkan pendekatan tradisional berdasarkan berat janjangan rata-rata (BJR) dengan mempertimbangkan tahun tanam dan luas area tanaman. Namun, tehnik ini kurang efektif dan efisien, Apabila perkiraan yang dibuat perusahaan salah berpotensi menyebabkan kerugian atau peningkatan anggaran produksi. Tujuan dari penelitian ini untuk mendapatkan perbandingan hasil peramalan pada bulan berikutnya dengan ukuran akurasi alpha terbaik menggunakan metode Single Exponential Smoothing. Metode yang digunakan dalam penelitian ini adalah berdasarkan data kualitatif dan kuantitatif dari hasil wawancara dan observasi data bulan desember 2022 - november 2023. Hasil peramalan dari ukuran akurasi nilai alpha 0.9 menggunakan metode Single Exponential Smoothing diperoleh peramalan untuk periode desember 2023 sebesar 13.835578,44 dengan tingkat persentase error MAPE sebesar 9,28%, MAD 1021423.6 dan MSE 174130366.Kata Kunci: kelapa sawit; peramalan; single exponential smoothing